Aboveground biomass production of Rhizophora apiculata Blume in Sarawak mangrove forest - Arianto, Chandra Iman; Gandaseca, Seca; Abu Hena, Mustafa Kamal (Science Publications, 2011)
Problem statement: Mangrove forests are found in tropical and subtropical coastal tidal regions. Rhizophora apiculata Blume is one of the most important species in mangrove forest. It is also one of the commercial mangrove timber species in Asia-Paciﬁc region which dominates large areas of mangrove in this region. In order to understand forest ecosystem characteristics and to establish the proper management system, a precise estimation of biomass is necessary. The objective of this study is to quantify the aboveground biomass production and stem volume of R. apiculata in Awat-Awat mangrove forest, Sarawak. Approach: Seven representative trees were used in this study for sampling from February 2011 to March 2011. Allometric relationships were examined using either independent variable Diameter (D) or combination of quadratic of D and Height (D2H). Results: The best fit of allometric equations were developed from the combination of quadratic of D and H (y = 0.055×0.948, R2 = 0.98) which is more recommended to estimate biomass and stem volume of R. apiculata in Awat-Awat mangrove forest, Sarawak. Total aboveground biomass and stem volume of R. apiculata were 116.79 t h−1 and 65.55 m3 h−1, respectively. Conclusion: Aboveground biomass and stem volume is closely related with tree diameter and height which indicates that aboveground biomass and stem volume will increase with increasing diameter and height of R. apiculata.